Supporting and Inhibiting Factors in the Implementation of the Child Friendly City (KLA) Policy by the Padang City Government as a Special Cluster in Padang City - Berliana, Hikmah Ainun; Alhadi, Zikri (The Future of Education Journal, 2026)
This study examines the factors influencing the implementation of the Child-Friendly City (Kota Layak Anak/KLA) policy in Padang City, focusing on the special protection cluster and drawing on George C. Edward III’s policy implementation framework. The KLA policy is a strategic public initiative aimed at fulfilling children’s rights and strengthening protection from violence, exploitation, neglect, and other forms of abuse. Using a descriptive qualitative approach, data were collected through in-depth interviews and document analysis involving officials from the Office of Women’s Empowerment and Child Protection, representatives of P2TP2A, and members of the Women and Children Protection Unit. The findings indicate that implementation is supported by a clear regulatory framework, institutional coordination, and the availability of child protection services. However, limited human and financial resources, weak cross-sectoral communication, low community participation, and uneven implementer commitment continue to hinder policy effectiveness. These factors significantly shape the performance of the special protection cluster in Padang City, underscoring the need to strengthen resources, enhance coordination, and improve institutional commitment.